Two types of remote-center-of-motion deployable manipulators with dual scissor-like mechanisms. (June 2021) - Yang, Yi; Liu, Hu; Zheng, Huayong; Peng, Yan; Yu, Yushu
Highlights: A generic remote-center-of-motion mechanism with dual scissor-like mechanisms. Two novel deployable manipulators using identical straight scissor-like elements. The decoupling designs, kinematics and singularities are discussed. Prototypes are manufactured, and motion experiments are conducted. Abstract: A generic structure for a planar remote center of motion (RCM) mechanism with dual scissor-like mechanisms is presented for the first time. Its mobility is analyzed using screw theory, and several specific planar RCM mechanisms composed of different scissor-like elements (SLEs) are proposed. Considering their ease of manufacture and feasibility, the main focus is on RCM mechanisms with identical straight SLEs. Two RCM deployable manipulators with two rotational and one translational degrees of freedom constructed from identical straight SLEs are proposed. The first has a stationary rotation center, which is fixed relative to the base platform, and an end-effector with large translation ability along the radial axis. The second has a mobile rotation center, which is fixed relative to the moving platform, and an end-effector with large translation ability along a specific axis. To decouple mechanically the rotation and translation of the end-effector, two actuators are designed specially to drive these manipulators. To evaluate the kinematics, the whole manipulators are decomposed into several components. The dexterity, inside singularity and workspaces are investigated. Finally, prototypes are manufactured, and experiments are conducted to validate the mobility and motion feasibility of these RCM deployable manipulators.